Identification of basketball parameters for a simulation model - Okubo, H.; Hubbard, M. (Procedia Engineering, 2010)
We estimate values of the coefficients of air drag, friction, stiffness and damping for a dynamic model of basketball shots by analyzing ball position and orientation using video data for basketball-rim and basketball-backboard bounce tests. The dynamic model can calculate any configuration change of a basketball during shots. The simulation model is compared to actual bounce tests and the parameters are determined from these experiments. The dynamic model with the identified parameters calculates a ball trajectory similar to the actual measured results. Stiffness and damping coefficients are determined from basketball-backboard bounce tests.